Word and witness an introduction to the gospel of John - Vargas, Niceta M. (Quezon City Ateneo de Manila University Press, 2013)
Narrative criticism, enlightened by historical-critical, socio-cultural, contextual and post-colonial approach on the gospel of John.
Includes bibliographical references (pages 327-333) and index.
In English.
Keywords: Bible. -- Introductions